The role of agriculture in local development through the example of Körösfő (Romania) - Ritter, Krisztián; Halmosi, Tímea; Péli, László (Studia Mundi – Economica, 2020)
The role of the endogenous resources has been emphasized since a long time by the literature of territorial and rural development. In parallel the role of agriculture in local employment has decreased significantly for the last few decades. The Institute for Regional Economics and Rural Development (IRERD) of the Szent István University Gödöllő regularly makes researches in traditionally farming rural villages to analyze the possible role of agriculture besides such tendencies in local development strategies. The primer sector has had a big importance for centuries in the life of Körösfő (Izvoru Crișului) village located near to Bánffyhunyad (Huedin). At the same time, the general tendencies, growing importance of local handwork industry and the decreasing farming opportunities have affected the settlement’s local economy as well. During a summer research camp in 2017 the role of agriculture as an endogenous competitive factor in long time local development was analyzed in this settlement by a primary research organized by the IRERD. According to the results, the agriculture has lost its previous significant role in the life of Körösfő caused by the changing economy of the village (trade and handwork), the disadvantaged conditions, the unfavourable natural capabilities Summing up the research, the sector could be the basis of creating local development strategy in Körösfő just in a very limited way.